Cybernet of parasites and parasitic diseases - Chun Jantanavivat (2016)
Joint International Tropical Medicine Meeting 1999: Century Park Hotel, Thailand 4-6 August 1999. Bangkok: Faculty of Tropical Medicine, Mahidol University; 1999. p.217.